PENGENDALIAN MANAJEMEN MODAL MANUSIA di PROGRAM STUDI: Sebuah Studi Fenomenologi - Wirawan ED Radianto; Helena Sidharta (Jurnal Manajemen Indonesia, 2015)
The purpose of this research is investigating how Head of Department implement management control in their real context. This research use phenomenology and in-depth interview for collecting data. This study found that Head of Department use many management control mechanism such as motivating, evaluation, giving opportunity, supporting, giving facilities, and role model. This research also found that department doesn't have specific mechanisms in order to implement management control